2019
DOI: 10.1016/j.ejso.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Hospital transfer after a breast cancer diagnosis: A population-based study in the Netherlands of the extent, predictive characteristics and its impact on time to treatment

Abstract: Exposure to early-life stress (ES) is associated with cognitive and metabolic deficits in adulthood. The role of early nutrition in programming these long-term effects is largely unknown. We focused on essential v-3 and v-6 long-chain polyunsaturated fatty acids (LCPUFA) and investigated whether ES affects central and peripheral FA profiles, as well as if and how an early diet with increased availability of v-3 LCPUFA (via lowering v-6/v-3 ratio) protects against ES-induced impairments. ES exposure [limited ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…Patients who changed hospital after surgery were less likely to receive adjuvant chemotherapy within 6 weeks, but not within 9 or 12 weeks. Although this concerned only 3·2 per cent of all patients, the association corroborates the theory that hospital transfer delays treatment, as shown by previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Patients who changed hospital after surgery were less likely to receive adjuvant chemotherapy within 6 weeks, but not within 9 or 12 weeks. Although this concerned only 3·2 per cent of all patients, the association corroborates the theory that hospital transfer delays treatment, as shown by previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…These referral patterns are not easily identified by NCR’s registrars, especially when time since diagnosis passes, probably resulting in a somewhat smaller number of identified DBR patients. However, in a study on IBR a 5% hospital transfer was seen [ 46 ], which implies little incompleteness in our study. Active follow-up for all patients in the NCR is advisable.…”
Section: Discussionmentioning
confidence: 69%
“…The SOs evaluated in the current study were provided in a tertiary hospital with high expertise on breast cancer care 6. Previous studies have suggested that expertise in treatments such as the use of NST and IBR might be indications for an SO or a change of hospital after diagnosis 9,29. This is partly true, as results from a national audit show that the use of NST and IBR in the NCI-AVL is above the national Dutch average 6.…”
Section: Discussionmentioning
confidence: 98%